Surf tourism. Concept, characterization, and competitiveness indicators. The case of Cape Town, South Africa. - Martín González, Roberto (UMA Editorial, 2024)
Sport tourism is one of the fastest-growing tourism segments. Amongst the wide variety of typologies of sport that can be practised, those ones that take place outdoors have experienced considerable growth. In fact, practising sport in natural environments is a worldwide growing trend. In the same vein, amongst these nature sports, surfing and its lifestyle have become distinctive elements of contemporary Western society. Moreover, surfers are well known to be highly mobile in the search of the places where it is possible to practise the sport, causing multiple impacts in all aspects of sustainability. The main aims of this thesis are two-fold. First, to understand the complexity of surf tourism not only to answer ‘what’ type of surfing-related-sports (SRSs), as well as ‘when’ and ‘where’ are they practised, but also ‘who’ is involved in the production, distribution, consumption, and the knowledge derived from it. Consequently, to investigate ‘who’ and ‘how’ is concerned in the creation of knowledge, reconceptualising surf tourism and indagating about its characterization. The second main objective is to construct an instrument to measure surf destination competitiveness considering the triple-bottom line of sustainability. These tools should be of interest not only for governmental and public institutions that deal with surf destinations, but also for private companies, non-governmental organisations (NGOs) and scholars, since it provides valuable information about the sources of knowledge, as well as economic, social, and environmental data to take managerial decisions.
Keywords: Turismo deportivo - Ciudad del Cabo (Sudáfrica) - Tesis doctorales; Sport tourism; Surf tourism; Competitiveness indicators; Sustainability